Transcriptome analysis in human breast milk and blood in a randomized trial after inactivated or attenuated influenza immunization - Elizabeth P. Schlaudecker; Travis L. Jensen; Casey E. Gelber; Phillip J. Dexheimer; Mark C. Steinhoff; David I. Bernstein; Johannes B. Goll (npj Vaccines)
Abstract Transcriptomic signatures were identified in human peripheral blood mononuclear cells (PBMCs) and breast milk lymphocyte (BML) cells induced by trivalent inactivated influenza vaccine (TIV) or live attenuated influenza vaccine (LAIV) administered after delivery. We performed an RNA-Seq analysis on blood and breast milk samples from a subset of subjects enrolled in a randomized, double-blind controlled study in breastfeeding women who received either intranasal LAIV and intramuscular placebo, or intramuscular TIV and intranasal placebo (LAIV, n = 10 and TIV, n = 6). Differentially expressed genes, gene clusters, and enriched pathways were identified. We observed increased innate immune signaling responses in BML but not in PBMC at Day 28 for the LAIV group. We hypothesize that breastfeeding extended the innate response to LAIV via mucosal immunity. An association between an increased IgG antibody response in TIV vs. LAIV identified in the parent study using ELISA corresponded to IGHG1 immunoglobulin gene expression in Day 28 PBMCs.